2002
DOI: 10.5194/angeo-20-1987-2002
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric vertical winds in the auroral oval/polar cap region

Abstract: Variations in mean hourly thermospheric winds and λ630 nm emission intensities show at least three significant associations between mean vertical winds and the auroral oval. Mean vertical winds within the auroral oval are smaller than those outside the oval, particularly those in the polar cap. A downward wind associated with entry of the observing region into the auroral oval can be seen in both Mawson and Davis hourly mean vertical winds. Large vertical winds are seen poleward of the auroral oval/polar cap b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…The resulting maps (not presented here) showed no clear pattern of mean wind variation, presenting instead an apparently random spread of small upward and downward velocities. These maps could not be considered equivalent to the results of Conde and Dyson [1995], Smith and Hernandez [1995], and Greet et al [2002]. It appears that either our analysis method, which attempted to correct for uncertainties in the WATS absolute zero-velocity reference by the application of a low-frequency rejection filter (as discussed earlier), was not adequate at the level required, or that the structures seen at $240 km do not extend to the mean height of the WATS observations ($450 km).…”
Section: Mean Vertical Windsmentioning
confidence: 89%
See 1 more Smart Citation
“…The resulting maps (not presented here) showed no clear pattern of mean wind variation, presenting instead an apparently random spread of small upward and downward velocities. These maps could not be considered equivalent to the results of Conde and Dyson [1995], Smith and Hernandez [1995], and Greet et al [2002]. It appears that either our analysis method, which attempted to correct for uncertainties in the WATS absolute zero-velocity reference by the application of a low-frequency rejection filter (as discussed earlier), was not adequate at the level required, or that the structures seen at $240 km do not extend to the mean height of the WATS observations ($450 km).…”
Section: Mean Vertical Windsmentioning
confidence: 89%
“…These data were obtained over a 2week interval of elevated K p . Recent work by Greet et al [2002] from four years of ground-based Fabry-Perot observations, also of the l630 nm oxygen emission, obtained at Mawson and Davis (invariant latitude $74.5°S) stations showed similar structures in hourly-mean thermospheric vertical winds, for example at Davis a diurnal variation of $ ±20 m s À1 was found at times of high K p . (The mean height of the l630 nm observations corresponds to $240 km, and hence is representative of a region below the majority of the WATS data.)…”
Section: Mean Vertical Windsmentioning
confidence: 91%
“…On the poleward edge of the nominal oval, Greet et al [2002] found that downward winds were observed on average in the early magnetic evening, with upward vertical winds near magnetic midnight. Greet et al [2002] also reported that vertical winds observed on the poleward edge of the auroral oval were of larger amplitude than those observed underneath the oval, again consistent with the bistatic results reported here.…”
Section: Discussionmentioning
confidence: 99%
“…In the polar cap, vertical winds of a few tens of m/s are common, and large upwellings up to 150 m/s are occasionally observed [Rees et al, 1984;Smith and Hernandez, 1995;Guo and McEwen, 2003;Ronksley, 2016]. Most studies reporting vertical winds in the thermosphere have been conducted in the auroral zone, where winds of up to 50 m/s are common [Wardill and Jacka, 1986;Crickmore et al, 1991;Crickmore, 1993;Conde and Dyson, 1995;Aruliah and Rees, 1995;Ishii et al, 1999Ishii et al, , 2001Greet et al, 2002;Anderson et al, 2012;Ronksley, 2016], but larger winds of 100 m/s or more have also been observed [Rees et al, 1984;Price et al, 1995;Innis et al, 1996Innis et al, , 1997Innis et al, , 1999Anderson et al, 2011]. Generally, downward winds have been seen on the equatorward edge of the auroral oval, and upward winds have been seen on the poleward edge.…”
Section: Introductionmentioning
confidence: 99%